Beyond the local turn: Local orderings and ordering of international organizations - Karolina Kluczewska; Anna Kreikemeyer (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2022)
It has become common knowledge that international organizations (IOs) are struggling with local ownership of their peacebuilding and development interventions worldwide. This happens despite the local turn which gained momentum in recent years in peacebuilding research and practice. Drawing on the post-liberal debate and area studies research focusing on conflict settlement, this paper argues that the continued difficulties of IOs to engage with the local needs to be seen in the context of multiple, diverse forms of ordering, namely structured and structuring processes of meaning-making and social interactions. To illustrate this argument, the paper refers to the case of Central Asia. Conceptualizing local orderings emerging from the ground up in communities which are targeted by internationally funded projects, on the one hand, and the underlying logic of ordering characterizing IOs and their interventions, on the other, allows us to see that there are structural differences between them. Following the Ethnographic Peace Research agenda, this paper compares these two ordering mechanisms by focusing on four specific components: cultural beliefs and norms, everyday practices, institutions, and issues of power.
urn:nbn:de:hbz:465-20220926-105206-8
Keywords: 320; Central Asia; ethnography; everyday peace; international development; international interventions; local orderings; peacebuilding; the local